Painting furniture. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows a paint shop at Portland, Oregon Assembly Center with evacuees brushing up an office desk and file box. The Portland Assembly Center was formerly known as the North Portland International Livestock Exposition Center.